Synthesis, Evaluation of Enzyme Inhibition and Redox Properties of Potential Dual COX-2 and 5-LOX Inhibitors - Jelena Bošković; Vladimir Dobričić; Marija Mihajlović; Jelena Kotur-Stevuljević; Olivera Čudina (MDPI AG, 2023)
Various dual inhibitors of COX-2 and 5-LOX enzymes have been developed so far in order to obtain more effective and safer anti-inflammatory drugs. The aim of this study was to design and synthesize new dual COX-2 and 5-LOX inhibitors, and to evaluate their enzyme inhibition potential and redox properties. Thirteen compounds (1-13) were designed taking into account structural requirements for dual COX-2 and 5-LOX inhibition and antioxidant activity, synthesized, and structurally characterized. These compounds can be classified as N-hydroxyurea derivatives (1, 2 and 3), 3,5-di-tert-butylphenol derivatives (4, 5, 6, 7 and 13), urea derivatives (8, 9 and 10) and "type B hydroxamic acids" (11 and 12). COX-1, COX-2 and 5-LOX inhibitory activities were evaluated using fluorometric inhibitor screening kits. The evaluation of the redox activity of newly synthesized compounds was performed in vitro in the human serum pool using redox status tests. The prooxidative score, the antioxidative score and the oxy-score were calculated. Seven out of thirteen synthesized compounds (1, 2, 3, 5, 6, 11 and 12) proved to be dual COX-2 and 5-LOX inhibitors. These compounds expressed good COX-2/COX-1 selectivity. Moreover, dual inhibitors 1, 3, 5, 11 and 12 showed good antioxidant properties.